Local Wisdom Learning Management of School Administrators under the Buriram Primary Educational Service Area Office 3: Local Wisdom Learning Management of School Administrators under the Buriram Primary Educational Service Area Office 3 - Tubsombut, Junjira; Vajarintarangoon, Kovit; Wongtongcharoen, Bunphot (RATANABUTH JOURNAL, 2025)
The objectives of the research were 1) to examine the current conditions and desired conditions and necessary needs, 2) to study guidelines for local learning management by school administrators. The research was divided into two phases. Phase I was to study the current and desired conditions and necessary needs. The sample group consisted of 328 teachers. The study used was a questionnaire. Data was analyzed using percentage, mean, standard deviation, and needs index. Phase II to study guidelines for local wisdom learning management by school administrators through interviewing five experts selected by purposive sampling. The results of the research were as follows: 1) The overall current conditions were at a moderate level. The aspect with the highest mean was promoting learning management by teachers. For the overall desired conditions, the aspect with the highest average was local curriculum evaluation. The need for local wisdom learning management of school administrators’ development can be prioritized as local curriculum evaluation, management of local learning resources, development in teaching, respectively. 2)The guidelines for developing local wisdom learning management by school administrators. These guidelines address four aspects. For Local Curriculum Management: School administrators should promote the preparation and storage of quality curriculum documents, learning materials and lesson plans. Local curriculum evaluation, school administrators should establish a comprehensive local curriculum evaluation system that involves teachers, students, parents, and the community. Management of local learning resources, school administrators should appoint a committee to manage and monitor the use of local learning resources. Development in teaching, school administrators should promote and develop teachers’ understanding and positive attitudes toward the local curriculum.